Studi Gambaran Histopatologis Hepar, Pulmo, Lien dan Otak serta Uji Serologis pada Tikus (Rattus norvegicus) yang diinfeksi Toxoplasma gondii - Sri Hartati; Slamet Raharjo; Irkham Widiyono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Toxoplasmosis is a parasitic disease caused by the intracellular obligate parasite of Toxoplasma gondii. Toxoplasma gondii (T. gondii) causes severe infections in infants or children who are congenitally infected and immunocompromised individuals. Rats are one source of natural transmission of toxoplasmosis in cats and cats will release oosysts with feces that will contaminate the environment that can be a source of transmission for other animals and humans. This study aims to determine the histopathological features of hepatic, pulmo, lienand cerebellum organ and serological tests in mice infected with T. gondii. Twenty rats of Wistar strains infected T. gondii strain RH stadium takizoit (107). On days 1, 3, 5, 7 and 15 post infection, mice were drawn blood forserological tests using commercial kit PastorexTM Toxo (Biorad, France). After the blood is taken, the rats are dietanized for liver organ samples, pulmo, lien and brain for histopathologic examination. The results showed thatserologic test was positive after the 5th postoperative day. The histopathologic results of day 1 postinfection appear to be takizoit T. gondii in the liver and brain. The formation of takizoit in the pulmo appears on the 7th day postinfection.